The origins and implementation of an intervention to support healthcare staff to deliver compassionate care: exploring fidelity and adaptation in the transfer of Schwartz Center Rounds® from the United States to the United Kingdom - Mary Leamy; Ellie Reynolds; Glenn Robert; Cath Taylor; Jill Maben (BMC, 2019)
Abstract Background Schwartz Center Rounds® (henceforce Rounds) were developed in the United States (US) in 1995 to provide a regular, structured time and safe place for staff to meet to share the emotional, psychological and social challenges of working in healthcare. Rounds were adopted in the United Kingdom (UK) in 2009 and have been subsequently implemented in over 180 healthcare organisations. Using Rounds as a case study, we aim to inform current debates around maintaining fidelity when an intervention developed in one country is transferred and implemented in another. Methods Interpretive design using nine qualitative interviews (UK = 3, US = 6) and four focus groups (UK: Focus group 1 (4 participants), Focus group 2 (5 participants; US: focus group 1 (5 participants) focus group 2 (2 participants) with participants involved in Rounds design and implementation, for example, programme architects, senior leaders, mentors and trainers. We also conducted non-participant observations of Rounds (UK = 42: USA = 2) and training days (UK = 2). Data were analysed using thematic analysis. Results We identified four core and seven sub-core Rounds components, based upon the US design, and seven peripheral components, based on our US and UK fieldwork. We found high core component fidelity and examples of UK adaptations. We identified six strategies used to maintain high fidelity during Rounds transfer and implementation from the US to UK settings: i) having a legal contract between the two national bodies overseeing implementation, ii) requiring adopting UK healthcare organisations to sign a contract with the national body, iii) piloting the intervention in the UK context, iv) emphasising the credibility of the intervention, v) promoting and evaluating Rounds, and vi) providing implementation support and infrastructure. Conclusions This study identifies how fidelity to the core components of a particular intervention was maintained during transfer from one country to another by identifying six strategies which participants argued had enhanced fidelity during transfer of Rounds to a different country, with contractual agreements and legitimacy of intervention sources key. Potential disadvantages include limitations to further innovation and adaptation.